2017
DOI: 10.1038/bmt.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy and autologous stem cell transplantation for primary central nervous system lymphoma: a multi-centre retrospective analysis from the United Kingdom

Abstract: The prognosis of patients with primary central nervous system lymphoma (PCNSL) has improved in recent years. This has partly been achieved by remission induction protocols incorporating high-dose methotrexate (HD-MTX) and rituximab. Given the high rates of relapse, consolidation therapy is usually considered in first response. Whole brain radiotherapy may prolong PFS but appears to confer no long-term survival advantage and is associated with significant neurocognitive dysfunction. Attempts to improve efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
(49 reference statements)
2
16
0
Order By: Relevance
“…Long‐term survival rates, however, are lower in chemorefractory patients who fail to achieve partial remission to induction therapy (Soussain et al , ; Schorb et al , ). Survival outcomes from the prospective studies have been mirrored by a recently published ‘real world’ UK retrospective study (Kassam et al , ).…”
Section: Consolidation Treatmentmentioning
confidence: 99%
“…Long‐term survival rates, however, are lower in chemorefractory patients who fail to achieve partial remission to induction therapy (Soussain et al , ; Schorb et al , ). Survival outcomes from the prospective studies have been mirrored by a recently published ‘real world’ UK retrospective study (Kassam et al , ).…”
Section: Consolidation Treatmentmentioning
confidence: 99%
“…Several retrospective studies have reported the efficacy of HDC-ASCT as a first-line treatment for PCNSL. [ 49 , 50 ] The IELSG32 study, a random phase 3 study, assigned 122 patients (1:1) to WBRT (45 Gy) and thiotepa-based HDC/ASCT and reported 2-year PFS rates of 80% and 69%, respectively, without significant difference between groups; however, long-term neurotoxicity was noted in the WBRT group. [ 51 ] In 2019, the ANOCEF-GOELAMS randomized phase II PRECIS study evaluated the efficiency and toxicity of WBRT and ASCT as first-line treatment in 140 younger patients (<60 years) assigned to receive WBRT or ASCT as consolidation therapy, with a conditioning regimen comprising TBC and a WBRT dose of 40 Gy.…”
Section: Consolidation Treatmentmentioning
confidence: 99%
“…Table 1 describes those studies that reported on HDC/ ASCT of >30 patients. These studies include phase II studies, 2 phase II randomized studies, and several large retrospective studies [24,26,31,[44][45][46][47][48][49]. Overall high remission rates and excellent long-term outcomes have been reported with approximately a 2-year PFS of 75-87% and a 2-year OS of 66-93% with a treatment-related mortality (TRM) of 0-11.5%.…”
Section: Consolidation With Hdc/asctmentioning
confidence: 99%